Comparison Of Polyphenol Antioxidant Levels In Fig Plant Leaves, Skin, And Flesh Using The DPPH Method - Annisa Ancha; Rachmat Faisal Syamsu; Iin Widya Ningsi; Armanto Makmun; Andi Millaty Halifah Dirgahayu Lantara (Jurnal EduHealth, 2025)
Fig plants (Ficus carica) are known to have potential as a source of antioxidants, especially from the polyphenol content found in the leaves, skin, and fruit flesh. This study aims to compare the antioxidant activity of polyphenols in three parts of the fig plant using the DPPH (2,2-diphenyl-1-picrylhydrazyl) test method to measure free radical inhibition. Extraction was carried out using 96% ethanol, and antioxidant activity was tested at concentrations of less than 100 ppm. The results showed that fig leaves had the highest antioxidant activity with an inhibition percentage of 75.991%, followed by fig flesh at 56.559%, and fig skin at 48.925%. ANOVA test analysis showed significant differences between the three parts of the plant with a significance value of p of 0.004 (<0.05), which confirmed that fig leaves have higher antioxidant potential than the skin and fruit flesh. This study provides useful information for the development of fig-based health products.